Substances used and prevalence rates of pharmacological cognitive enhancement among healthy subjects - Franke, Andreas G.; Bagusat, Christiana; Rust, Sebastian; Engel, Alice; Lieb, Klaus (European archives of psychiatry and clinical neuroscience, 2014)
Pharmacological “cognitive enhancement” (CE) is defined as the use of any psychoactive drug with the purpose of enhancing cognition, e.g. regarding attention, concentration or memory by healthy subjects. Substances commonly used as CE drugs can be categorized into three groups of drugs: (1) over-the-counter (OTC) drugs such as coffee, caffeinated drinks/energy drinks, caffeine tablets or Ginkgo biloba; (2) drugs being approved for the treatment of certain disorders and being misused for CE: drugs to treat attention-deficit/hyperactivity disorder (ADHD) such as the stimulants methylphenidate (MPH, e.g. Ritalin ® ) or amphetamines (AMPH, e.g. Attentin ® or Adderall ® ), to treat sleep disorders such as modafinil or to treat Alzheimer’s disease such as acetylcholinesterase inhibitors; (3) illicit drugs such as illicit AMPH, e.g. “speed”, ecstasy, methamphetamine (crystal meth) or others. Evidence from randomized placebo-controlled trials shows that the abovementioned substances have limited pro-cognitive effects as demonstrated, e.g. regarding increased attention, increased cognitive speed or shortening of reaction times, but on the same time poses considerable safety risks on the consumers. Prevalence rates for the use of CE drugs among healthy subjects show a broad range from less than 1 % up to more than 20 %. The range in prevalence rates estimates results from several factors which are chosen differently in the available survey studies: type of subjects (students, pupils, special professions, etc.), degree of anonymity in the survey (online, face-to-face, etc.), definition of CE and substances used/misused for CE, which are assessed (OTC drugs, prescription, illicit drugs) as well as time periods of use (e.g. ever, during the past year/month/week, etc.). A clear and comprehensive picture of the drugs used for CE by healthy subjects and their adverse events and safety risks as well as comprehensive and comparable international data on the prevalence rates of CE among healthy subjects are of paramount importance for informing policy makers and healthcare professionals about CE.